Modern Teaching Methods and its Effects (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
New teaching methodologies are changing the educational environments around the world and driving better academic performance among students. This article will examine over some of the main innovative approaches that educators have forged over the last few years and that every 21st century teacher should be acquainted with.